Tobacco Mosaic Viral Nanoparticle Inhibited Osteoclastogenesis Through Inhibiting mTOR/AKT Signaling - Shan Z (Dove Medical Press, 2020)
Zhongshu Shan,1,2,* Hongtao Bi,3,* Angxiu Suonan,2 Yong Gu,1 Huan Zhou,4 Kun Xi,1 Rui Xiong,5 Hua Chen,2 Liang Chen1 1Department of Orthopedic Surgery, The 1st Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 2Department of Orthopedic Surgery, People’s Hospital of Qinghai Province, Xining, Qinghai, People’s Republic of China; 3Qinghai Provincial Key Laboratory of Tibetan Medicine Pharmacology and Safety Evaluation, Northwest Institute of Plateau Biology, Chinese Academy of Sciences, Xining, Qinghai, People’s Republic of China; 4Department of Radiography, Rocket Army Specialty Medical Center, Beijing, People’s Republic of China; 5Nutrition Department, People’s Hospital of Qinghai Province, Xining, Qinghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liang ChenDepartment of Orthopedic Surgery, The 1st Affiliated Hospital of Soochow University, 188 Shizi St. Suzhou, Jiangsu 215006, People’s Republic of ChinaEmail chenliangspine@163.comIntroduction: Tobacco mosaic virus-based nanoparticles (TMV VNPs) were previously shown to promote osteogenic differentiation in vitro. This study aims to investigate whether and how TMV VNPs impact on osteoclastogenesis in vitro and bone injury healing in vivo.Methods: Raw264.7 cells were cultured in osteoclastogenic medium in culture plates coated with or without TMV and TMV-RGD1 VNPs, followed by TRAP staining, RT-qPCR and WB assessing expression of osteoclastogenic marker genes, and immunofluorescence assessing NF-κB activation. TMV and TMV-RGD1-modified hyaluronic acid hydrogel were used to treat mouse tibial bone injury. Bone injury healing was checked by micro-CT and Masson staining.Results: TMV and TMV-RGD1 VNPs significantly inhibited osteoclast differentiation and downregulated the expression of osteoclastogenic marker genes Ctr, Ctsk, Mmp-9, Rank, and Trap. Moreover, TMV and TMV-RGD1 VNPs inhibited NF-κB p65 phosphorylation and nuclear translocation, as well as activation of mTOR/AKT signaling pathway. TMV and TMV-RGD1-modified HA hydrogel strongly promoted mouse tibial bone injury with increased bone mass compared to plain HA hydrogel. The amount of osteoclasts was significantly reduced in TMV and TMV-RGD1 treated mice. TMV-RGD1 was more effective than TMV in inhibiting osteoclast differentiation and promoting bone injury repair.Discussion: These data demonstrated the great potential of TMV VNPs to be developed into biomaterial for bone injury repair or replacement.Keywords: tobacco mosaic virus, viral nanoparticle, osteoclast, mTOR, tibial bone injury